Trichoplax and the origin of animal complexity - Schierwater, Bernd (Henry Stewart Talks, 2016)
Trichoplax and the origin of animal complexity, Complex patterns usually evolve from more basic patterns, Introducing the placozoan Trichoplax, Metazoan – definition, The Biology of Placozoa, Trichoplax adhaerens: Grell clone, Comparing Placozoa with other Metazoa, Parallel evolution: diploblasts & triploblasts, The new Placula hypothesis, Hox-like genes